2016
DOI: 10.5812/modernc.10297
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS High Risk Behaviors and Necessity of Prevention in the Population of Birjand, East of Iran 2013 to 2014: A Population-Based Study

Abstract: Background: Human immunodeficiency virus (HIV)/ acquired immune deficiency syndrome (AIDS) is a major threat for public health around the world. Objectives: This study aimed at investigating the prevalence of HIV/ADIS high risk behaviors and necessity of prevention in the population of Birjand, East of Iran. Methods: This population-based study was conducted on 5235 subjects from Birjand, East of Iran, during years 2013 to 2014. Subjects were asked to complete a checklist including gender, marital status, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…It is noteworthy that in this study, six participants (0.2%) were reported as suspected of having HTLV-1 infection. Furthermore, the sero-prevalence of anti-HIV, anti-HCV, anti-HBc and HBsAg, as reported in our previous studies, were 0% (95% CI: 0-0.001), 0.2% (95% CI: 0-0.036), 15% (95% CI: 0.086-0.235) and 1.6% (95% CI: 0.002-0.07), respectively (5,13,15). Also, the results of the PCR confirmed 7 cases out of 10 people with anti-HCV positive, and so the actual prevalence of HCV was reported at 0.14%.…”
Section: Sero-prevalence Of Virusessupporting
confidence: 78%
See 2 more Smart Citations
“…It is noteworthy that in this study, six participants (0.2%) were reported as suspected of having HTLV-1 infection. Furthermore, the sero-prevalence of anti-HIV, anti-HCV, anti-HBc and HBsAg, as reported in our previous studies, were 0% (95% CI: 0-0.001), 0.2% (95% CI: 0-0.036), 15% (95% CI: 0.086-0.235) and 1.6% (95% CI: 0.002-0.07), respectively (5,13,15). Also, the results of the PCR confirmed 7 cases out of 10 people with anti-HCV positive, and so the actual prevalence of HCV was reported at 0.14%.…”
Section: Sero-prevalence Of Virusessupporting
confidence: 78%
“…Furthermore, the sero-prevalence of anti-HIV, anti-HCV, anti-HDV, anti-HBc and HBsAg in our previous studies was reported at 0%, 0.2%, 1.2%, 15% and 1.6%, respectively. 5,[13][14][15] The results of our studies show that the prevalence of bloodborne viral infection in South Khorasan is close to that observed in the overall Iranian population. [16][17][18] However, the prevalence of HTLV-1 was 10 times lower than North and Razavi Khorasan provinces (0.3% vs. 2-3%), 11 and even 4 times lower than a segregated population in this region close to South Khorasan.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation